Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-22157-5
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and eye size evolution of the ogre-faced spiders

Abstract: Net-casting spiders (Deinopidae) comprise a charismatic family with an enigmatic evolutionary history. There are 67 described species of deinopids, placed among three genera, Deinopis, Menneus, and Asianopis, that are distributed globally throughout the tropics and subtropics. Deinopis and Asianopis, the ogre-faced spiders, are best known for their giant light-capturing posterior median eyes (PME), whereas Menneus does not have enlarged PMEs. Molecular phylogenetic studies have revealed discordance between mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 157 publications
0
6
0
Order By: Relevance
“…This is most strikingly apparent in Deinopidae, where the high predicted rate of evolution in the PMEs (Figure 6) results from the secondary reduction of PME diameter in Menneus (Chamberland et al, 2022). Despite speculation that this might enable niche separation between nocturnal Deinopis and crepuscular Menneus , both have been observed foraging at night (Chamberland et al, 2022). Additional structural changes to the eye further support lower sensitivity in Menneus PMEs (Blest et al, 1980), indicating a reduced contribution of vision to hunting in this genus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is most strikingly apparent in Deinopidae, where the high predicted rate of evolution in the PMEs (Figure 6) results from the secondary reduction of PME diameter in Menneus (Chamberland et al, 2022). Despite speculation that this might enable niche separation between nocturnal Deinopis and crepuscular Menneus , both have been observed foraging at night (Chamberland et al, 2022). Additional structural changes to the eye further support lower sensitivity in Menneus PMEs (Blest et al, 1980), indicating a reduced contribution of vision to hunting in this genus.…”
Section: Discussionmentioning
confidence: 94%
“…The authors reported stronger negative allometry in the AMEs than the ALEs or PLEs, suggesting some flexibility in growth dynamics between eye pairs. In addition, the potential complexity of phylogenetic visual allometry in spiders was recently highlighted in Deinopidae: in the context of reconstructing the evolution of their enlarged PMEs, Chamberland et al (2022) also reported lower AME diameters which, though statistically non-significant, further hint at a role for modularity and possible trade-offs in the evolution of eye size. However, this has yet to be explored from a broader comparative perspective.…”
Section: Introductionmentioning
confidence: 97%
“…Megadiverse lineages, such as arachnids, are perhaps the best suited to study nuances of biogeography in part directly due to their diversity (high resolution tools, redundancies that may compensate for incomplete sampling), and (often) abundance (relative ease of intensive sampling without great impact on populations). The growing emphasis on invertebrate biogeography, where various arachnids play an important role (Boyer et al, 2007;Opatova et al, 2013;Fernańdez and Giribet, 2015;Chamberland et al, 2018;Nogueira et al, 2019;Pfingstl et al, 2019;Chamberland et al, 2020;Chamberland et al 2022;Cain et al, 2021;Derkarabetian et al, 2021;Santibañez-López et al, 2021;Monjaraz-Ruedas et al, 2022), demonstrates the opportunities that lie ahead in the field.…”
Section: Grand Challenge 1 Assess Arachnid Species Richness For Compa...mentioning
confidence: 99%
“…anchored hybrid enrichment (Lemmon et al, 2012) or the ultraconserved elements (Faircloth et al, 2012). An increasing number of studies on arachnids are demonstrating that these techniques are able to resolve both deep and shallow divergencies (Hamilton et al, 2016;Maddison et al, 2017;Starrett et al, 2017;Kuntner et al, 2019;Kulkarni et al, 2020;Xu et al, 2021;Chamberland et al, 2022;Li et al, 2022). These data should continue to be accumulated with the ultimate goal of openness and compatibility of datasets.…”
Section: Grand Challenge 2: Standardize Arachnid Systematics Researchmentioning
confidence: 99%